2019
DOI: 10.1111/dom.13710
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world prevalence of the inclusion criteria for the LEADER trial: Data from a national general practice network

Abstract: Aims To explore the prevalence and describe the clinical characteristics of people with type 2 diabetes with a similar cardiovascular (CV) profile to that of the LEADER trial participants in a primary care setting in England. Materials and methods In this cross‐sectional analysis, using the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) network database, we identified people with type 2 diabetes meeting the LEADER inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…However, a majority of eligible patients remain untreated with these medications 9 . Our findings of low prevalent use of GLP‐1RAs and SGLT2is despite trial eligibility are consistent with prior reports 21–24 . Low utilization of GLP‐1RAs and SGLT2is, despite large‐scale cardiovascular outcomes trials showing efficacy published as early as 2015, may be related to unfamiliarity with the drugs, a lack of knowledge regarding their cardiovascular benefits, hesitancy to prescribe additional medications, reluctance to overstep traditional specialist prescriber roles for diabetes therapy, and the cost of therapy 24–26 .…”
Section: Discussionsupporting
confidence: 80%
“…However, a majority of eligible patients remain untreated with these medications 9 . Our findings of low prevalent use of GLP‐1RAs and SGLT2is despite trial eligibility are consistent with prior reports 21–24 . Low utilization of GLP‐1RAs and SGLT2is, despite large‐scale cardiovascular outcomes trials showing efficacy published as early as 2015, may be related to unfamiliarity with the drugs, a lack of knowledge regarding their cardiovascular benefits, hesitancy to prescribe additional medications, reluctance to overstep traditional specialist prescriber roles for diabetes therapy, and the cost of therapy 24–26 .…”
Section: Discussionsupporting
confidence: 80%
“…Overall, GLP‐1RAs and SGLT‐2is consistently appear to have strong benefits on major adverse CV events, especially in patients with a history of cardiovascular disease (CVD) 44 . We recognize that long‐term data on the use of SGLT‐2is and GLP‐1RAs are limited, and that a minority of patients seen in routine clinical practice would satisfy trial enrolment criteria 45–47 . However, data from real‐world studies (reviewed in Newman et al 36 ) strongly support the evidence gathered from RCTs and univocally suggest that CV and renal benefits extend to the routine care population and in patients with a comparatively lower CV risk.…”
Section: The Changing Scenariomentioning
confidence: 96%
“…Also, physicians' or patients' adoption of new drugs may not be as fast as expected due to uncertain long-term real-world drug effectiveness and safety evidence. For instance, a recent study found that less than 10% of the real-world patients who had comparable CVD risks with the participants in the Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER) trial were actually prescribed with liraglutide [5]. Moreover, GLP-1ra is administrated by subcutaneous injection, which likely discourages physicians or patients from the early initiation of GLP-1ra until a therapy with multiple oral GLAs has failed.…”
Section: Introductionmentioning
confidence: 99%